2018
DOI: 10.1371/journal.pone.0203366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various kinetic parameters of CA-125 in patients with advanced-stage ovarian cancer undergoing neoadjuvant chemotherapy

Abstract: Various kinetic parameters of serum CA-125 have been reported to have better correlation with outcomes for patients treated with neoadjuvant chemotherapy (NAC). This study aimed to compare the available kinetic parameters of serum CA-125 in an external cohort of advanced-stage ovarian cancer. Using the cancer registry databases from the Yonsei Cancer Hospital, we retrospectively reviewed 210 patients with advanced-stage ovarian cancer, treated with NAC followed by interval debulking surgery. We compared area u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The Gynecologic Cancer Intergroup (GCIG) defined the CA-125 response as a 50% reduction in CA-125 levels maintained for at least 28 days, in patients treated for recurrent diseases [49,50]. Different studies, including a recent analysis of the ICON-8 phase III trial dataset showed that this criterion was inadequate for assessing the efficacy of the neoadjuvant chemotherapy and predicting the benefit from IDS [48,51,52].…”
Section: Indicators Of Tumor Primary Chemosensitivitymentioning
confidence: 99%
“…The Gynecologic Cancer Intergroup (GCIG) defined the CA-125 response as a 50% reduction in CA-125 levels maintained for at least 28 days, in patients treated for recurrent diseases [49,50]. Different studies, including a recent analysis of the ICON-8 phase III trial dataset showed that this criterion was inadequate for assessing the efficacy of the neoadjuvant chemotherapy and predicting the benefit from IDS [48,51,52].…”
Section: Indicators Of Tumor Primary Chemosensitivitymentioning
confidence: 99%
“…The predictive values of CA-125 decline percentages during treatments were extensively investigated, with inconsistent outcomes (3)(4)(5)(6). The Gynecologic Cancer Intergroup (GCIG) defined the CA-125 response as a 50% reduction in CA-125 levels maintained for at least 28 days, in patients treated for recurrent diseases (7).…”
Section: Main Text: 3277 Words (Max 5000 Words) Introductionmentioning
confidence: 99%
“…CA-125 reduction may be used to predict the chemotherapy response in the neoadjuvant environment. Patients who do not respond to CA-125 also do not experience IDS and have a poor prognosis [1][2][3][4][5][6].…”
Section: Figure 4: Histopathological Appearance Of Serous Cystadenoca...mentioning
confidence: 99%
“…The only routine biomarker used to assess the status of the disease and monitor the success of chemotherapy in patients with epithelial ovarian cancer is cancer antigen-125 (CA-125). The value of CA-125 is expected to correlate with neoadjuvant chemotherapy (NACT) response in the neoadjuvant situation, where the effects of surgery are absent [ 4 - 6 ]. We present a case of serous papillary cystadenocarcinoma of the ovary in a 50-year-old patient and its treatment by NACT and debulking surgery [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%